2000
DOI: 10.1095/biolreprod62.5.1322
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Antrum Formation of Bovine Preantral Follicles in Long-Term Culture In Vitro1

Abstract: Culture of preantral follicles has important biotechnological implications through its potential to produce large quantities of oocytes for embryo production and transfer. A long-term culture system for bovine preantral follicles is described. Bovine preantral follicles (166 +/- 2.15 micrometer), surrounded by theca cells, were isolated from ovarian cortical slices. Follicles were cultured under conditions known to maintain granulosa cell viability in vitro. The effects of epidermal growth factor (EGF), insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
193
2
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(216 citation statements)
references
References 35 publications
6
193
2
8
Order By: Relevance
“…In contrast, the other treatments (FSH-7d and FSH + FGF-2) were effective in maintaining follicle ultrastructural integrity up to day 7. Our light histological results confirm earlier studies in which FSH maintained preantral follicle viability after short (Matos et al, 2007a andMatos et al, 2007c) or long-term culture (Cortvrindt et al, 1997, Wright et al, 1999and Gutierrez et al, 2000. It is suggested that the absence of FSH in the medium could compromise the diffusion of several essential chemical and physical factors through the basement membrane (Hsueh et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, the other treatments (FSH-7d and FSH + FGF-2) were effective in maintaining follicle ultrastructural integrity up to day 7. Our light histological results confirm earlier studies in which FSH maintained preantral follicle viability after short (Matos et al, 2007a andMatos et al, 2007c) or long-term culture (Cortvrindt et al, 1997, Wright et al, 1999and Gutierrez et al, 2000. It is suggested that the absence of FSH in the medium could compromise the diffusion of several essential chemical and physical factors through the basement membrane (Hsueh et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, an extended culture period may be required for a follicle to develop to the preovulatory stage. Few long-term in vitro culture studies have achieved follicular activation, i.e., the transition from primordial to primary follicles (ovine: Muruvi et al, 2005; human: Otala et al, 2002 andSadeu et al, 2006) or the development of antral follicles (bovine: Gutierrez et al, 2000;mouse: Mitchell et al, 2002). Recently, Gupta et al (2008) produced buffalo embryos after the long-term culture of isolated large secondary follicles.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence showing that IGF-I plays a key role in the development of preantral follicles and in the process of follicular atresia. When added during in vitro culture of preantral follicles, IGF-I has been shown to stimulate follicular growth in humans (12), cattle (13), rats (14), and mice (15) in synergy with follicle-stimulating hormone. In the rat, IGF-I added during in vitro preantral follicular culture significantly increased follicular diameter and DNA content (14).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report that demonstrates the maintenance of caprine preantral follicle survival using histological and ultrastructural analysis, even after longterm culture (14 d) in domestic animals. Other studies related antrum formation in goats [28], cattle [29], and mice [30], and in the production of embryos [31] from in vitro culture of preantral follicles. It is important to mention that these studies used the large, advanced stage of secondary preantral follicles.…”
Section: Discussionmentioning
confidence: 99%